ANALISIS DAYA GUNA AMPAS TAHU DARI PABRIK TAHU LIN’S KUOK SEBAGAI SUMBER PROTEIN PAKAN SAPI POTONG - Harfina Rais (Jurnal Teknik Industri Terintegrasi, 2021)
Feed is important component in the livestock industry. Feed quality provide optimal production in this industry, and vice versa. The cost of feed can reach 60-85% of the cost of production, so the emphasis on feed costs needs to be considered. Industrial waste has the potential to be used as a source of feed, one of which is waste from a tofu factory, namely tofu dregs. Tofu dregs contain high crude protein and high palatability value. The high potential of tofu dregs to be used as a source of animal feed, prompted researchers to conduct a study on the potential use of tofu dregs from the Lin's Kuok tofu factory as a source of protein in beef cattle rations. The results showed that Lin's Kuok Tofu Factory's production of tofu dregs in % DM was 31.44 Kg/day CP, CP 9.53 Kg/day, TDN 24.49 Kg/day. The usability of tofu dregs from Lin's Kuok Tofu Factory is (DM) 5.03 AU, CP 14.44 AU and TDN 5.69 AU. Keywords: Rations; Tofu Dregs; Feed animal.